Post-collisional 1.75 Ga mantle-derived felsic magmatism in the Cauaburi Orogeny, NW Amazon Craton, Brazil - Marcelo Almeida; Moacir José Buenano Macambira; Túlio Amós de Araújo Mendes; João Orestes Schneider Santos (Journal of the Geological Survey of Brazil, 2023)
In the Amazon NW craton, ~1.75 Ga granites are commonly found inboard (eastern) the Cauaburi Magmatic Arc (1.81-1.76 Ga, flare-up phase), generated during the final stages of retreat of the arc westward, a process that lasted approximately 80 million years. This magmatism is more abundant in the Northeastern Domain (Marauiá and Marié-Mirim suites), exhibiting higher volumes in more exhumed areas and elongated shapes suggesting structural control (Imeri Terrain). These granites are locally deformed in shear zones under high strain rates (Dn+2) and metamorphism with greenschist to epidote-amphibolite facies conditions (K´Mudku Shear Belt). The granites in this region are characterized as peralkaline to peraluminous, ferroan and alkalic to calc-alkaline, with chemical signatures consistent with A-type magmas. In the Southwestern Domain (Tiquié Suite), these granites occur in smaller volumes, with subcircular shapes and contemporaneous volcanism (Cachoeira do Machado Formation), suggesting emplacement on higher crustal levels (Uaupés Terrain). They are also deformed under lower strain rates (Dn+3?) and low greenschist facies conditions (Traíra Shear Belt). These granites are metaluminous, ferroan to magnesian, and alkalic-calcic, showing Nb-Ta negative anomalies, suggesting transitional characteristics between I-type and A-type granites ("ambiguous" granites). All of these granitic suites are enriched in SiO2 (70-76%) and high-field strength elements (HFSE), contain dissolved OH–F-bearing fluids and exhibit a range of magma oxidation states, from reduced in the Marié-Mirim Suite to oxidized in the Marauiá and Tiquié suites. The magmas are derived from a depleted source, or sources containing an important mantle input (εNd +2.27 to +0.92), with temperature models suggesting ranges from 1205oC to 1085oC. The granites origins probably involve partial melting of lower crustal quartz feldspathic igneous or charnockite sources (Tiquié and Marauiá suites) and differentiation of tholeiitic mafic sources with low contributions of crustal sources (Marié-Mirim Suite), showing metallic fertility mineral potential for Sn, Ta, Nb and probably other rare metals and gemstones. These granites may have been generated from a model based on a late-orogenic magmatism (post-collisional), arc-related, associated with an extensional tectonics, probably produced by underplating in a back-arc setting, or during the gravitational collapse of the Cauaburi orogen (post-1.78 Ga), involving mantle-derived magmas uprising and partial melting with low crustal sources interactions.